Cover Image. (4th March 2021) - Ma, Mary‐Jane L.; Yakovenko, Sergey; Zhang, Haiqiang; Cheng, Suk Hang; Apryshko, Valentina; Zhavoronkov, Alex; Jiang, Peiyong; Chan, K. C. Allen; Chiu, Rossa W. K.; Lo, Y. M. Dennis
Abstract : The cover image is based on the Original Article Fetal mitochondrial DNA in maternal plasma in surrogate pregnancies: Detection and topology by Mary†Jane L. Ma et al., https://doi.org/10.1002/pd.5860 .